The Students' Perception on Utilizing Spotify Podcast for Improving EFL Speaking Skill: - - Widya; Suryanti, Dwi Retno; Sundari, Hanna (International Journal of English Language and Pedagogy, 2024)
The purpose of this research was to figure out what students thought about using podcasts to improve their speaking skills. To investigate students' perceptions, the researcher utilized a qualitative technique using a basic interpretative design. This research included two students. They are from various high school students in the academic year 2022/2023. The information was acquired through a semi-structured interview. The researcher used thematic analysis to get the data. According to the findings of this research, researchers classified two aspects: speaking skills and podcast benefits. The findings should indicate that students had a favorable opinion of the use of podcasts in learning to speak. Students considered podcasts to be engaging media since they have a variety of materials or themes to which they may listen and practice their speaking whenever they want. The researcher also hopes that students will agree that podcasts are useful for speaking achievement, such as increasing vocabulary and word pronunciation.